Influence of hydrophilic/hydrophobic diols on the properties of polyurethane hydrogels: solvent-free one-pot synthesis - Divakaran, Anumon V.; Nair, Sanoop B.; Karambe, Shivani S.; Wadgaonkar, Prakash P.; Nair, Kiran Sukumaran; Badiger, Manohar V. (Journal of Materials Chemistry B, 2025)
Herein, we report the design and synthesis of bio-degradable porous polyurethane hydrogels by a green, solvent-free, one-pot technique that can withstand physiological mechanical loads and aid in tissue regeneration. The hydrophilic/hydrophobic nature of the hydrogel was tuned using diols such as polycaprolactone diol (PCL) and polycarbonate diol (PCD), in combination with polyethylene glycol (PEG, MW approximate to 4000 g mol-1), 4,4 `-methylene bis(cyclohexyl isocyanate) (H12MDI) and hexanetriol (HT), which served as crosslinking agents. The structural characterizations of the hydrogels were performed using FT-IR as well as 1H and 13C high resolution magic angle spinning nuclear magnetic resonance (HR-MAS) spectroscopy. The utilization of various diols in the synthesis of the hydrogels enabled precise control over crystallinity, pore sizes, and customization of mechanical and degradation properties. These hydrogels exhibited tensile strength in the range of 0.22-1.48 MPa, while their compressive strength varied from 0.92 to 29.3 MPa. In vitro degradation profiles in the presence and absence of the enzyme Amano lipase PS revealed that the degradation process is contingent upon the specific diol present in the hydrogel. Furthermore, preliminary in vitro biological experiments confirmed the biocompatibility of the gels, indicating their potential as suitable substrates for drug delivery applications. This diverse library of gels can be shaped into specific forms, highlighting their promising applications as scaffolds and implants in drug delivery systems and tissue engineering.